Characteristics associated with Lactobacillus iners-dominated vaginal microbiota. (8th September 2021) - Novak, Juliano; Ravel, Jacques; Ma, Bing; Ferreira, Carolina Sanitá Tafner; Tristão, Andrea da Rocha; Silva, Marcia Guimaraes; Marconi, Camila
Abstract : Objective: The protective role of Lactobacillus iners in the vaginal microbiota has been questioned. Recent studies have shown that L. iners is the dominating taxon in a large subset of women worldwide. The aim of this study was to identify sociodemographic, behavioural and clinical variables associated with L. iners -dominated community state type (CST) III in Brazilian women of reproductive age. Participants and methods: This study leveraged microbiota compositional data generated by sequencing of the V3-V4 16S rRNA gene from vaginal samples collected from 442 participants enrolled in a previous cross-sectional study that included 609 women in five geographical regions of Brazil. A total of 167 (27.4%) participants were excluded from the current study as they did not present a Lactobacillus -dominated vaginal microbiota. Data on sociodemographic and behavioural characteristics of the study population were obtained through face-to-face interviews. Participants were assigned to two study groups: those with L. iners -dominated CST III (n=222) and those with three distinct CSTs (I, II or V) dominated by another Lactobacillus spp. (n=220). Logistic regression analysis using a stepwise method was performed to test association between CST III and participants' characteristics, considering their OR and 95% CIs. Results: Among the population characteristics assessed, L. iners -dominated CST III was independently associated with having two or more sexual partners (OR 3.27; 95% CI 1.50 to 7.11) and microscopic detection of Candida sp. on vaginal smears (OR 2.24; 95% CI 1.02 to 4.89). Other characteristics were inversely associated with CST III, including condom use (OR 0.59; 95% CI 0.38 to 0.91), higher educational level (OR 0.61; 95% CI 0.41 to 0.91) and diet containing milk/dairy intake (OR 0.43; 95% CI 0.20 to 0.90). Conclusion: Unprotected sex practices, number of sexual partners and lower educational levels may be useful for identifying women with L. iners- dominated microbiota and its suboptimal protective properties. L. iners microbiota does not seem to provide optimal protection against Candida sp. colonisation, warranting further investigation.